2015
DOI: 10.1111/pde.12577
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Aphthous Stomatitis in Childhood and Adolescence: A Single‐Center Experience

Abstract: Our study is consistent with previous reports in terms of clinical features of aphthous ulcers, related diseases, and family history of RAS, but no associated laboratory abnormalities were noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
4
12
2
1
Order By: Relevance
“…4,28,29 In this research, 46.4% of the students had a family history of RAS. This percentage is higher than the one presented by Gürkan et al, 15 where 35.8% of the patients had a family history of RAS. This difference might be explained by the fact that the studied age groups were more limited in the present research (3-11 years) in comparison with the ones studied by Gürkan et al 15 (2-17 years).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…4,28,29 In this research, 46.4% of the students had a family history of RAS. This percentage is higher than the one presented by Gürkan et al, 15 where 35.8% of the patients had a family history of RAS. This difference might be explained by the fact that the studied age groups were more limited in the present research (3-11 years) in comparison with the ones studied by Gürkan et al 15 (2-17 years).…”
Section: Discussioncontrasting
confidence: 64%
“…This percentage is higher than the one presented by Gürkan et al, 15 where 35.8% of the patients had a family history of RAS. This difference might be explained by the fact that the studied age groups were more limited in the present research (3-11 years) in comparison with the ones studied by Gürkan et al 15 (2-17 years). The present study also revealed that, of both parents, the mother seemed to contribute more to the family history of this condition.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…We read with interest the article describing the clinical features of recurrent aphthous stomatitis (RAS) in children and adolescents (1). RAS is one of the most common oral mucosal diseases.…”
Section: Recurrent Aphthous Stomatitis As a Marker Of Celiac Disease mentioning
confidence: 99%
“…We thank Marty et al for their valuable comments on our article (1). Recurrent aphthous stomatitis (RAS) is a common oral mucosal disease with an unknown etiology.…”
Section: Response To "Recurrent Aphthous Stomatitis As a Marker Of Cementioning
confidence: 99%